The extent of change of the policies and principles of the International Monetary Fund after 2008 global financial crisis - Tasmaganbetov, A.B.; Ganchev, G.T.; Аkhmetova, G.І.; Zhanseitov, A.T. (BUKETOV BUSINESS REVIEW, 2019)
This paper has been divided into several sections in which it scrutinizes the extent at which the principle and policies of IMF have changed with respect to the 2008 global financial crisis. In spite of diverse economic and political situations under which crises occurred during different times of history, particular features common to all crises are revealed. The rapidly evolving global economy, as well as new challenges with economic and social implications make the problem of financial crises, including currency crises, extremely important in the current situation. Especially given the fact that the crises affect various countries and regions of the world. Serious currency crashes have occurred in developing countries with marked structural problems, but also in mature economies which possess fully developed market mechanisms and efficient systemic solutions. In addition, the severely destructive impact on the global financial balance and the scale of potential losses caused by such turbulences indicate that there is a need for a responsible and effective preventive policy on all decision-making levels. It seems that adequate responses and actions on the global level, in addition to actions simultaneously taken by regional organizations and by various countries themselves, can be a basis for creating conditions conducive both to the stabilization of the entire global economy and to its sustainable growth. This article looks into the conceptualization of the performance of IMF in the crisis, highlighting its role, limits of output performance, and utility as metrics of evaluation.